Old Classics Anew – Reflections on the study of Compo - Korae, Eva; Achilleos, Konstantina Niina; Vënëlainen, Tuomas (My University, 2025)
This project sprung from the hypothesis that if the way we produce today is largely a consequence of the Industrial Revolution, then the re-introduction of pre-industrial techniques into modern systems of manufacture might bear some solutions to the problem of waste and overproduction. As the radical abandonment of these smaller scale techniques appears to have led to the destruction of the planet’s resources, we as craftsmakers aim to test how previous recipes can be reworked to fit in the contemporary household. We are studying techniques used to produce well-preserved antique furniture made in mainland Europe. Cyprus, as a British colony, hosted several of them. These techniques may today seem gruesome or unethical since they involve the use of animal bones and rabbit skin, but could the actual products be disposed of as nutritious additions to household compost? We are attempting to make a product in the way gilded furniture were made in 19th-century France, as we understand that local Cypriot makers used similar techniques to produce gilded mirror frames through local resources. The artefact chosen to embody this study is a replica of the classic Anglepoise 90, which is technically very specific and also an icon of industrialised design. This popular product bears decades of contextualization, raising fruitful conversations between the team members during the re-making process. At the moment the arising research questions contemplate whether the material called “Compo” can be successfully 3D printed in a clay extruder or even laser cut, in addition to traditional casting and moulding. Furthermore we ask ourselves whether the production can be scaled up without falling into modern-day production oversights. This study describes our process to remix, remake, implement and decolonize old material recipes and techniques towards achieving a highly technical, functional lamp through a glocal scope.
Keywords: Compo, Biodegradable, Product Design, Sustainability